Baculovirus Insecticides in Latin America: Historical Overview, Current Status and Future Perspectives - Haase, Santiago (2015)
Baculoviruses are known to regulate many insect populations in nature. Their host-specificity is very high, usually restricted to a single or a few closely related insect species. They are amongst the safest pesticides, with no or negligible effects on non-target organisms, including beneficial insects, vertebrates and plants. Baculovirus-based pesticides are compatible with integrated pest management strategies and the expansion of their application will significantly reduce the risks associated with the use of synthetic chemical insecticides. Several successful baculovirus-based pest control programs have taken place in Latin American countries. Sustainable agriculture (a trend promoted by state authorities in most Latin American countries) will benefit from the wider use of registered viral pesticides and new viral products that are in the process of registration and others in the applied research pipeline. The success of baculovirus-based control programs depends upon collaborative efforts among government and research institutions, growers associations, and private companies, which realize the importance of using strategies that protect human health and the environment at large. Initiatives to develop new regulations that promote the use of this type of ecological alternatives tailored to different local conditions and farming systems are underway